Uptake of vaccination in pregnancy. (October 2021) - Sebghati, Mercede; Khalil, Asma
Abstract: Maternal immunisation is a public health strategy that aims to provide protection against certain infections to both mother and her foetus or newborn child. Vaccination of pregnant women induces vaccine-specific antibodies that lead to the subsequent transfer of these antibodies across the placenta or through breastfeeding to the offspring. At present, vaccinations in pregnancy are limited to pertussis, tetanus, diphtheria, polio, and the seasonal Influenza vaccine. Recently, some countries have incorporated routine antenatal vaccinations in their national immunisation programmes. Future vaccines targeted at pregnant women such as respiratory syncytial virus (RSV) and Group B streptococcus (GBS) are under development. The recently approved Covid-19 vaccines have no safety data for use in pregnancy at present, but have been considered in the UK in extremely vulnerable pregnant women or pregnant frontline health and social care workers. In this article, we review the evidence supporting maternal immunisation and discuss the uptake of vaccines in pregnant women, challenges of recording the data on vaccine coverage, and consider reasons behind the present levels of uptake and strategies for future improvements. Highlights: Maternal immunisation is a public health strategy providing protection against infections to mothers and their foetuses. Influenza and pertussis immunisations in pregnancy are incorporated into routine vaccination programmes in some countries. We review the evidence supporting these immunisations in pregnancy and discuss uptake rates. Discussion of the challenges of recording data on maternal vaccine coverage. Consideration of reasons behind current levels of vaccine uptake and strategies for future improvements.